Perconditioning combined with postconditioning on kidney ischemia and reperfusion - Costa,Felipe Lobato da Silva (2017)
Abstract Purpose: To evaluate if combination of perconditioning and postconditioning provides improved renal protection compared to perconditioning alone in a model of renal reperfusion injury. Methods: Thirty rats were assigned into 6 groups: normality; sham; ischemia and reperfusion; postconditioning; perconditioning; perconditioning + postconditioning. Animals were subjected to right nephrectomy and left renal ischemia for 30 minutes. Postconditioning consisted of 3 cycles of 5 min renal perfusion followed by 5 min of renal ischemia after major ischemic period. Perconditioning consisted of 3 cycles of 5 min hindlimb ischemia followed by 5 min of hindlimb perfusion contemporaneously to renal major ischemic period. After 24 hours, kidney was harvested and blood collected to measure urea and creatinine. Results: Perconditioning obtained better values for creatinine and urea level than only postconditioning (p<0.01); performing both techniques contemporaneously had no increased results (p>0.05). Regarding tissue structure, perconditioning was the only technique to protect the glomerulus and tubules (p<0.05), while postconditioning protected only the glomerulus (p<0.05). Combination of both techniques shows no effect on glomerulus or tubules (p>0.05). Conclusions: Perconditioning had promising results on ischemia and reperfusion induced kidney injury, enhanced kidney function and protected glomerulus and tubules. There was no additive protection when postconditioning and perconditioning were combined.